Interpretative Phenomenological Analysis Penerimaan Orang Tua terhadap Anak Pecandu Alkohol - Fitri Rahmadani; Ayu Anjelina; Miksa Denola Dusatri; Zuliana Wijaya (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Alcohol abuse is a serious issue that not only affects the individual experiencing addiction but also has profound consequences for families, particularly parents. Parents often face significant emotional, social, and psychological burdens when dealing with a child struggling with alcohol dependence. This study aims to gain an in-depth understanding of parental acceptance of children with alcohol addiction. The research employed a qualitative phenomenological approach with two parents as participants, each having a child with alcohol dependence. Data were collected through semi-structured interviews, which allowed for a rich exploration of personal experiences, and analyzed using the Interpretative Phenomenological Analysis (IPA) technique. The thematic analysis revealed six major themes: the dynamics of parent–child interactions, emotional responses of parents, changes in the child’s behavior due to addiction, the influence of parents’ past experiences, self-harming behavior as a coping mechanism, and the normalization of the child’s behavior. Findings indicate that parents’ past experiences, including trauma and parenting patterns, strongly influenced how they accepted their child’s condition. Furthermore, maladaptive coping strategies, such as self-harm, emerged as part of the acceptance process when parents faced situations beyond their control. This study underscores the importance of trauma-informed family interventions to help parents develop healthier coping mechanisms. It also highlights the need for comprehensive psychoeducational programs that involve all family members to foster resilience and mutual support. In doing so, the research contributes to the development of more effective psychological support systems for families affected by alcohol addiction.